Bioplastic from Corn Starch; Characteristic and Biodegradable Performance (International Journal of Scientific Research in Science and Technology, 2025)
For food packaging plastics are generally used. Raw materials having good mechanical properties, cheap, lightweight and simple in the manufacturing process are used for polymers and plastics. Whereas the many plastics are not easily biodegradable. Therefore, innovators and other communities are worried to overcome the problems occurring due to non-biodegradable plastics which is making an adverse effect on the environment, so the more emphasis is given to produce the biodegradable plastic for day to day needs use. So, bioplastics are the mostly demanded and required entity because they are generally biodegradable, and using natural resources and will reduce the environmental pollution. To manufacture bioplastic starch-based material is mostly used. Due to it added natural fibres increases the strength of bioplastic and better degradation process of the bioplastic in soil. The additional properties of bioplastic like, tensile strength, stiffness, capacity to be used for purposes are the more advantageous. In this paper process of corn starch bioplastic, its characteristic study and its better possibilities of degradation due to corn starch biodegradable plastic with natural fibre are described. Which will give the scope in future to innovative ideas for material component as a natural fibre for bioplastic manufacturing.